Fixed-Nitrogen Loss Associated with Sinking Zooplankton Carcasses in a Coastal Oxygen Minimum Zone (Golfo Dulce, Costa Rica) - Stief, Peter (2017)
Oxygen minimum zones (OMZs) in the ocean are of key importance for pelagic fixed-nitrogen loss (N-loss) through microbial denitrification and anaerobic ammonium oxidation (anammox). Recent studies document that zooplankton is surprisingly abundant in and around OMZs and that the microbial community associated with carcasses of a large copepod species mediates denitrification. Here, we investigate the complex N-cycling associated with sinking zooplankton carcasses exposed to the steep O2 gradient in a coastal OMZ (Golfo Dulce, Costa Rica). 15N-stable-isotope enrichment experiments revealed that the carcasses of abundant copepods and ostracods provide anoxic microbial hotspots in the pelagic zone by hosting intense anaerobic N-cycle activities even in the presence of ambient O2. Carcass-associated anaerobic N-cycling was clearly dominated by dissimilatory nitrate reduction to ammonium (DNRA) at up to 30.8 nmol NH+4 individual−1 d−1, followed by denitrification (up to 10.8 nmol N2-N individual−1 d−1), anammox (up to 1.6 nmol N2-N individual−1 d−1), and N2O production (up to 1.2 nmol N2O-N individual−1 d−1). In contrast, anaerobic N-cycling mediated by free-living bacteria proceeded mainly through anammox and denitrification in the anoxic bottom water, which underpins the distinctive microbial metabolism associated with zooplankton carcasses. Pelagic N-loss is potentially enhanced by zooplankton carcasses both directly through N2 and N2O production, and indirectly through NH+4 production that may fuel free-living anammox bacteria. We estimate that in the hypoxic water layer of Golfo Dulce, carcass-associated N2 and N2O production enhance N-loss as much as 1.4-fold at a relative carcass abundance of 36%. In the anoxic bottom water, however, N-loss is likely enhanced only marginally due to high ambient rates and low zooplankton abundance. Thus, zooplankton carcasses may enhance N-loss mainly at the hypoxic boundaries of OMZs which are usually more extensive in open-ocean than in coastal settings. Notably, these contributions by zooplankton carcasses to pelagic N-loss remain undetected by conventional, incubation-based rate measurements.